RANCANG BANGUN APLIKASI MONITORING ANAK DI PONDOK PESANTREN TAFRIIJUL AHKAM CIKIRAY BERBASIS ANDROID - Rizki Fatullah; Masum Masum; Ma'mun Amri (Program Studi Sistem Informasi, Universitas Banten Jaya, 2021)
This research was conducted to make it easier for parents to get fast and realtimeactivity information, plus the lack of data storage on student activity by caregivers. In this modern era, the development of technology is increasing rapidly so that everything is computerized, so the cottage needs to follow the development of this modern era, so that the work in the cottage will be easy and reduce errors due to human error. As technology develops, website-based applications for child monitoring have started to emerge, but parents are already using smartphones a lot, with the existence of Android-based applications, it is hoped that it can be used as a monitoring medium for children that can be accessed by all parents who leave their children at the Tafriijul Islamic boarding school. Ahkam Cikiray effectively and efficiently. This application uses the waterfall method and uses UML (Unified Modeling Language) for visual modeling systems. The data collection process was carried out by interviewing the boarding school. The conclusion of making this application is to make it easier for the guardian of students to receive information on weekly, monthly, yearly activities and this system makes it easier for teachers at the Tafriijul Ahkam Islamic boarding school to provide information on activities, achievements, memorization of the Qur'an, violations of spp payments and payment of re-registration to parents, so the lodge does not spend a lot of money to provide information on student activities by letter.